Multisocietal consensus on the use of cytoreductive surgery and HIPEC for the treatment of diffuse malignant peritoneal mesothelioma: a GRADE approach for evidence evaluation and recommendation - Kusamura, Shigeki; Cinquini, Michela; Morris, David; Piso, Pompiliu; Kindler, Hedy; Brandl, Andreas; Levine, Edward; Glehen, Olivier; Kepenekian, Vahan; Sgarbura, Olivia; Sugarbaker, Paul H.; Baratti, Dario; et al. (Journal of surgical oncology, 2025)
The Peritoneal Surface Oncology Group International (PSOGI) previously issued a recommendation endorsing cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) for treating diffuse malignant peritoneal mesothelioma (DMPM). However, broader acceptance of this approach, particularly within some segments of medical oncology, remains limited. To address this, PSOGI initiated a multisociety consensus effort, involving multidisciplinary International Societies, to strengthen and expand the endorsement of CRS-HIPEC for DMPM. Using the GRADE ADOLOPMENT approach, the expert panel systematically reviewed existing guidelines and evaluated the available evidence to reinforce the recommendation. The panel unanimously recommended CRS-HIPEC for a carefully selected subset of DMPM patients, emphasizing that this approach offers the best potential for improved survival compared to systemic chemotherapy alone. Despite the very low certainty of evidence, a strong recommendation was issued, reflecting the panel's recognition of the life-threatening feature of DMPM and the limited efficacy of systemic chemotherapy. This consensus also highlights the importance of centralized and expert-driven care. The recommendation aligns with previous guidelines and underscores the critical need for broader acceptance of this treatment strategy in managing this rare and aggressive malignancy.